Simulation of the clinical and pathological manifestations of Coronavirus Disease 2019 (COVID-19) in golden Syrian hamster model: implications for disease pathogenesis and transmissibility - Chan, Jasper Fuk-Woo (Clin Infect Dis, 2020)
BACKGROUND: A physiological small animal model that resembles COVID-19 with low mortality is lacking. METHODS: Molecular docking on the binding between angiotensin-converting enzyme 2 (ACE2) of common laboratory mammals and the receptor-binding domain of the surface spike protein of SARS-CoV-2 suggested that the golden Syrian hamster is an option. Virus challenge, contact transmission, and passive immunoprophylaxis were performed. Serial organ tissues and blood were harvested for histopathology, viral load and titre, chemokine/cytokine assay, and neutralising antibody titre. RESULTS: The Syrian hamster could be consistently infected by SARS-CoV-2. Maximal clinical signs of rapid breathing, weight loss, histopathological changes from the initial exudative phase of diffuse alveolar damage with extensive apoptosis to the later proliferative phase of tissue repair, airway and intestinal involvement with virus nucleocapsid protein expression, high lung viral load, and spleen and lymphoid atrophy associated with marked cytokine activation were observed within the first week of virus challenge. The lung virus titre was between 10(5)-10(7) TCID(50)/g. Challenged index hamsters consistently infected naïve contact hamsters housed within the same cage, resulting in similar pathology but not weight loss. All infected hamsters recovered and developed mean serum neutralising antibody titre ≥1:427 fourteen days post-challenge. Immunoprophylaxis with early convalescent serum achieved significant decrease in lung viral load but not in lung pathology. No consistent non-synonymous adaptive mutation of the spike was found in viruses isolated from infected hamsters. CONCLUSIONS: Besides satisfying the Koch’s postulates, this readily available hamster model is an important tool for studying transmission, pathogenesis, treatment, and vaccination against SARS-CoV-2.